RhIII‐Catalyzed C−H Activation: Mizoroki–Heck‐Type Reaction of Maleimides. Issue 7 (30th May 2018) - Bettadapur, Kiran R.; Sherikar, Mahadev Sharanappa; Lanke, Veeranjaneyulu; Prabhu, Kandikere Ramaiah
Abstract: Maleimides are not known to undergo oxidative‐Heck reaction because they lack a syn ‐periplanar β‐hydrogen atom. Herein, we report a C−H activation‐based Mizoroki–Heck‐type reaction of maleimides using ketone as the directing group. The reaction utilizes a Rh III ‐catalyst along with Ag2 CO3 as the oxidant to carry out a base‐mediated formal β‐hydride elimination. Abstract : Maleimides are not known to undergo oxidative Heck reaction because they lack a syn ‐periplanar β‐hydrogen atom. Herein, we report the first C−H activation‐based oxidative Heck reaction of maleimides using ketone as the directing group. The reaction utilizes a Rh III catalyst along with Ag2 CO3 as the oxidant to carry out a base‐mediated formal β‐hydride elimination.